(3GdNSGQI GdHMQjI GdeTJQcIs - (3WGQb(B, (3Sjas ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2003)
(3gPG GdcJGH jJfGhd ehVhY GdNSGQI GdHMQjI GdeTJQcI (B( (3GdYhGQjI GdYGeI (B) (3OQGSI JaUjdjI dbhGYO jhQc (B- (3GfJhQjH (B1994- (3eaghe GdYhGQjI GdYGeI (B- (3GfhGY GdNSGQGJ GdHMQjI (B- (3GdGUhd GdbGfhfjI h GdJGQjNjI ddYhGQjI GdYGeI (B- (3GdYhGQjI GdYGeI h GdTQjYI GdGSdGejI (B- (3TQM eaUd dbhGYO jhQc GfJhQjH (B1994 (3h GfJbGOGJgG (B- (3bhGYO jhQc GfJhQjH (B1994 (3h GdJdhK GdHMQj (B- (3GSdhH JShjI GdYhGQjI GdYGeI (B- (3JShjI GdYhGQjI GdYGeI aj MGdI GdSaf GdeSJGLQI (B- (3GdYhGQjI GdYGeI HSfOGJ GdTMf h eTGQWGJ GdGjLGQ eY YOO ef GdGeKdI GdMSGHjI h GdMGdGJ GdJWHjbjI(B.s
Keywords: (3GdSaf (B- (3MhGOKs; (3GdYbhO GdHMQjIs; (3GdbGfhf GdOhdj GdHMQjs; (3Gdfbd GdHMQjs